Comparative Analysis of e-Learning and u-Learning Environments in Corporate Training - Mohamad Trio Febriyantoro; Rifki Zaitul Ikhlas; Rashid Rahman; Shahinur Rahman (Journal of Social Science Utilizing Technology, 2024)
Background. The rapid evolution of digital technologies has significantly impacted corporate training methods. Traditional e-learning environments have been widely adopted, yet the emergence of ubiquitous learning (u-learning) presents a shift towards more flexible, context-aware learning experiences. Despite the growing interest, limited studies provide a comparative analysis between e-learning and u-learning in corporate settings. Purpose. This research aims to evaluate and compare the effectiveness of e-learning and u-learning environments in corporate training, focusing on learner engagement, content delivery, and overall performance. Method. A mixed-methods approach was used, combining quantitative surveys and qualitative interviews with corporate employees who participated in both e-learning and u-learning training programs. Data were collected across several multinational companies, and analyzed using statistical tools to identify performance trends and engagement metrics. Results. Findings reveal that u-learning environments enhance learner engagement and adaptability due to their flexibility in accessing content across diverse devices and contexts. Conversely, e-learning showed better outcomes in structured, course-driven scenarios but lacked the same level of interaction and contextual learning. Conclusion. The study concludes that u-learning environments provide a more personalized and engaging training experience, particularly for employees with diverse learning needs. Organizations should consider integrating u-learning strategies alongside traditional e-learning for more dynamic corporate training programs.